2012
DOI: 10.1590/s1517-83822012000100022
|View full text |Cite
|
Sign up to set email alerts
|

Screening of actinomycetes from earthworm castings for their antimicrobial activity and industrial enzymes

Abstract: Actinomycetes from earthworm castings were isolated and screened for their antimicrobial activity and industrial enzymes. A total of 48 isolates were obtained from 12 samples of earthworm castings. Highest numbers of isolates were recovered from forest site (58.33 %) as compared to grassland (25%) and agricultural land (16.66%). The growth patterns, mycelial coloration of abundance actinomycetes were documented. The dominant genera Identified by cultural, morphological and physiological characteristics were St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 14 publications
(14 reference statements)
0
10
0
3
Order By: Relevance
“…Actinomycetales genera Streptomyces, Rathayibacter, Nocardioides, Agromyces and Rhodococcus have been associated with the soil and earthworm cast and gut. The genus Streptomyces has antimicrobial activity and enzyme production capability in the earthworm gut (59). Furthermore, Streptomyces caeruleus has been found to help earthworms in organic matter metabolism and plant material decomposition (60).…”
Section: Unique Bacterial Indicators As Potential Biomarkers Of Exposure To CDmentioning
confidence: 99%
“…Actinomycetales genera Streptomyces, Rathayibacter, Nocardioides, Agromyces and Rhodococcus have been associated with the soil and earthworm cast and gut. The genus Streptomyces has antimicrobial activity and enzyme production capability in the earthworm gut (59). Furthermore, Streptomyces caeruleus has been found to help earthworms in organic matter metabolism and plant material decomposition (60).…”
Section: Unique Bacterial Indicators As Potential Biomarkers Of Exposure To CDmentioning
confidence: 99%
“…A majority of these isolates produced industrially important enzymes such as amylases, proteases, gelatinases, lipases, DNases, cellulases, ureases and phosphatases. On another occasion, Kumar et al (2012) have isolated actinomycetes from earthworm castings and have screened them for antimicrobial activities and industrial enzymes. Streptomyces, Streptosporangium, Saccharopolyspora, Nocardia, Micromonospora, Actinomadura, Microbispora, Planobispora and Nocardiopsis were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the findings with results from several studies, we observed that our strains are well producers, considering their production abilities of the enzymes studied. For instance, in a research conducted by Kumar et al (2012), the authors aimed to screen actinomycetes for antimicrobial activity and industrial enzymes, and obtained forty-eight strains from earthworm castings. They screened them for the production of five enzymes including amylase, caseinase and lipase, and reported that only ten isolates produced all the enzymes studied.…”
Section: Production Of Alkaline Enzymesmentioning
confidence: 99%